Managerial subcultures in Turkey: how does membership in business associations impact managerial values and assumptions?. (26th March 2007) - Aycan, Zeynep; Kirmanoglu, Hasan
The study examines the impact of membership in business associations on managerial subcultures in Turkey. Perceptions of societal values and assumptions of top level managers regarding how to manage human resources were compared between the two groups: members of Independent Industrialists and Businessmen's Association (IIBA) and members of other business associations. IIBA member organisations are known for their adherence to conservative Islamic values and principles, while others stand closer to the secular ideology. A total of 223 top level managers (Presidents and Vice Presidents) participated in the study. Results indicated that top managers did not differ in their values and assumptions.